Enhancing the internal plant colonization rate with endophytic nitrogen-fixing bacteria - Kovtunovych, G.; Lar, O.; Kordyum, V.; Kleiner, D.; Kozyrovska, N. (Биополимеры и клетка, 1999)
Several diazotrophic strains of Klebsiella oxytoca and K. terrigena that colonize the plant-host interior were able to produce the plant cell wall depolymerising enzyme pectate lyase (Pel). The activity of the K. oxytoca enzyme was weaker than that of phytopathogenic bacteria, and it was located mainly inside the cells. A small fraction of the cells (10⁻⁶ to 10⁻⁵) in populations grown in nonselective media was able to grow in a selective medium with polygalactorunate (PC) as sole carbon source. After passage through selective medium cells were converted to the Pet+ -phenotype, and total Pet-activity in population of K. oxytoca increased. The increased level of Pelactivity of K. oxytoca and K. terrigena correlated with a 10-fold higher rate of internal colonization of wheat roots. Cultures of K. oxytoca VN13 grown in selective medium with PG also showed increased stimulation of wheat growth. Seedlings inoculated with such cultures exhibited better development resulting in higher biomass.